DINAMIKA RESILIENCE KELUARGA PENDERITA SKIZOFRENIA DENGAN KEKAMBUHAN - Wahyu Widiastutik* Indah Winarni** Retno Lestari *** (Universitas Muhammadiyah Jember, 2016)
This research discusses the resilience dinamic of skizofrenia sufferer with the fall which aims to explore the feeling of the family about the resiliece dinamic of skizofrenia sufferer with the fall. This research metodology uses qualitatif approach which involves 6 participants. The data analysis uses interpretative phenomenological analysis. The informative method uses in-depth interview technique with their parents and other relatives. They treat and understand the patient well. This research pruduces 8 topic namely : (1) the family of the sufferer knew skizofrenia as a mental illness; (2) going to the alternative services to cure the illness; (3) they regarded which was experienced as bad-given; (4) they received the risk of situation.Keywords : resilience, skizofrenia, kekambuhan